Real-time approach to tunnelling in open quantum systems: Decoherence and anomalous diffusion - Calzetta, Esteban Adolfo (2006)
Macroscopic quantum tunnelling is described using the master equation for the reduced Wigner function of an open quantum system at zero temperature. Our model consists of a particle trapped in a cubic potential interacting with an environment characterized by dissipative and normal and anomalous diffusion coefficients. A representation based on the energy eigenfunctions of the isolated system, i.e. the system uncoupled to the environment, is used to write the reduced Wigner function, and the master equation becomes simpler in that representation. The energy eigenfunctions computed in a WKB approximation incorporate the tunnelling effect of the isolated system and the effect of the environment is described by an equation that is in many ways similar to a Fokker-Planck equation. Decoherence is easily identified from the master equation and we find that when the decoherence time is much shorter than the tunnelling time the master equation can be approximated by a Kramers-like equation describing thermal activation due to the zero point fluctuations of the quantum environment. The effect of anomalous diffusion can be dealt with perturbatively and its overall effect is to inhibit tunnelling. © 2006 IOP Publishing Ltd.